Reflecting on the global burden of musculoskeletal conditions: lessons learnt from the Global Burden of Disease 2010 Study and the next steps forward. Issue 1 (9th June 2014) - Hoy, Damian G; Smith, Emma; Cross, Marita; Sanchez-Riera, Lidia; Blyth, Fiona M; Buchbinder, Rachelle; Woolf, Anthony D; Driscoll, Tim; Brooks, Peter; March, Lyn M
Abstract : The objective of this paper is to provide an overview of the strengths, limitations and lessons learned from estimating the burden from musculoskeletal (MSK) conditions in the Global Burden of Disease 2010 Study (GBD 2010 Study). It should be read in conjunction with the other GBD 2010 Study papers published in this journal. The strengths of the GBD 2010 Study include: the involvement of a MSK expert group; development of new and more valid case definitions, functional health states, and disability weights to better reflect the MSK conditions; the extensive series of systematic reviews undertaken to obtain data to derive the burden estimates; and the use of a new, more advanced version of the disease-modelling software (DisMod-MR). Limitations include: many regions of the world did not have data; the extent of heterogeneity between included studies; and burden does not include broader aspects of life, such as participation and well-being. A number of lessons were learned. Ongoing involvement of experts is critical to ensure the success of future efforts to quantify and monitor this burden. A paradigm shift is urgently needed among global agencies in order to alleviate the rapidly increasing global burden from MSK conditions. Prevention and control of MSK disability are required, along with health system changes. Further research is needed to improve understanding of the predictors and clinical course across different settings, and the ways in which MSK conditions can be better managed and prevented.